1975
DOI: 10.1007/bf01070839
|View full text |Cite
|
Sign up to set email alerts
|

Cholangitis complicating congenital hepatic fibrosis

Abstract: A patient with cholangitis complicating congenital hepatic fibrosis is presented. In contrast to most other reported cases, many of whom have been treated surgically, this patient had a benign course. The likelihood that this complication of congenital hepatic fibrosis will respond to appropriate conservative therapy suggests that more aggressive forms of treatment should be reserved for those patients who fail to respond to medical management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1978
1978
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Ten patients developed esophageal varices, four patients had live‐threatening gastrointestinal bleeding, and four patients received portosystemic shunts, which is consistent with the diagnosis of congenital hepatic fibrosis [Alvarez et al, 1981; Ghisan and Younoszai, 1981]. Different clinical variants of congenital hepatic fibrosis have been described: a form solely with portal hypertension, a cholangiopathic form, and a mixed portal hypertensive‐cholangiopathic form [Howlett et al, 1975; Perisic, 1995]. The pathogenic basis of the disease seems to be a progressive destructive cholangiopathy, resulting in a fetal type of biliary fibrosis [Desmet, 1992a].…”
Section: Discussionmentioning
confidence: 82%
“…Ten patients developed esophageal varices, four patients had live‐threatening gastrointestinal bleeding, and four patients received portosystemic shunts, which is consistent with the diagnosis of congenital hepatic fibrosis [Alvarez et al, 1981; Ghisan and Younoszai, 1981]. Different clinical variants of congenital hepatic fibrosis have been described: a form solely with portal hypertension, a cholangiopathic form, and a mixed portal hypertensive‐cholangiopathic form [Howlett et al, 1975; Perisic, 1995]. The pathogenic basis of the disease seems to be a progressive destructive cholangiopathy, resulting in a fetal type of biliary fibrosis [Desmet, 1992a].…”
Section: Discussionmentioning
confidence: 82%
“…Previously, Howlett et al [9] reported the case of a 5-month-old girl with story of unknown fever and hepatosplenomegaly. Liver biopsy showed CHF with acute suppurative cholangitis.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The culture of the specimen was sterile. kidney; and acute cholangitis secondary to bacterial infection of the dilated intrahepatic bile ducts (3,4,6).…”
Section: Case Reportmentioning
confidence: 99%
“…Increased erythrocyte sedimentation rate, hypergammaglobulinemia, and his-Congenital hepatic fibrosis (CHF) is a rare autosomal recessive disease of children and young adults which is characterized by peculiar histological lesions of the liver and by kidney abnormalities, such as renal tubular ectasias or .. infantile" polycystic kidney disease (l ,2). Acute bacterial infection of dysplastic intra-or, less frequently, .extrahepatic bile ducts is one of the main complications of CHF (3,4). We now report the case of a boy .afflicted with CHF who developed severe hypoxemia due to pulmonary arteriovenous fistulas 7 years after a portocaval shunt.…”
mentioning
confidence: 95%